Respuesta :

gmany

Answer:

d : e : f = 4 : 3 : 6

Step-by-step explanation:

[tex]\bold{METHOD\ 1}\\\\6d=8e\qquad\text{divide both sides by 6}\\\\d=\dfrac{8}{6}e\to d=\dfrac{4}{3}e\\\\\text{Substitute it and}\ f=2e\ \text{to the ratio}\ d:e:f:\\\\\dfrac{4}{3}e:e:2e\qquad\text{cancel}\ e\\\\\dfrac{4}{3}:1:2\qquad\text{multiply by 3}\\\\\huge\boxed{4:3:6}[/tex]

[tex]\bold{METHOD\ 2}\\\\6d=8e\qquad\text{divide both sides by 6}\\\\d=\dfrac{8}{6}e\qquad\text{divide both sides by}\ e\neq0\\\\\dfrac{d}{e}=\dfrac{4}{3}\to d:e=4:3\\\\2e=f\qquad\text{divide both sides by 2}\\\\e=\dfrac{f}{2}\to e=\dfrac{1}{2}f\qquad\text{divide both sides by}\ f\neq0\\\\\dfrac{e}{f}=\dfrac{1}{2}\to e:f=1:2\\\\\text{We have}\ d:e=4:3\ \text{and}\ e:f=1:2.[/tex]

[tex]\text{We know}\ \dfrac{1}{2}=\dfrac{1\cdot3}{2\cdot3}=\dfrac{3}{6}\\\\\text{threfore}\ e:f=3:6\\\\\text{Now we have}\\\\\left\begin{array}{ccc}d:e=4:3\\e:f=3:6\end{array}\right\}\large{\boxed{d:e:f=4:3:6}}[/tex]